2016
DOI: 10.1007/s13311-015-0394-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies for Immune-Mediated Myopathies: A Current Perspective

Abstract: Summary Until recently, the treatment of immune-mediated inflammatory myopathies has largely been empirical with glucocorticoids, steroid-sparing immunosuppressive drugs, and intravenous immunoglobulin. However, a proportion of patients are only partially responsive to these therapies, and there has been a need to consider alternative treatment approaches. In particular, patients with inclusion body myositis are resistant to conventional immunotherapies or show only a transient response, and remain a major cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 136 publications
0
11
0
Order By: Relevance
“…Propensity score matching was performed using a greedy propensity score algorithm without replacement 24. RCI patients were matched with other patients by five digits of propensity score.…”
Section: Methodsmentioning
confidence: 99%
“…Propensity score matching was performed using a greedy propensity score algorithm without replacement 24. RCI patients were matched with other patients by five digits of propensity score.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most important considerations of immunosuppressive drug therapy is the increased risk of serious or life-threatening infections. [1][2][3] Earlier studies in inflammatory muscle disease have shown that 27%-37% of patients acquire significant infections, many of which are caused by opportunistic pathogens. 4,5 Furthermore, these studies demonstrated that increased risk of infection was associated with various immunomodulatory treatments, including corticosteroids, azathioprine, and immunoglobulin therapies.…”
mentioning
confidence: 99%
“…The mainstay of treatment for autoimmune neuromuscular disorders is immunotherapy aimed at modulating or reducing disease activity. One of the most important considerations of immunosuppressive drug therapy is the increased risk of serious or life‐threatening infections . Earlier studies in inflammatory muscle disease have shown that 27%–37% of patients acquire significant infections, many of which are caused by opportunistic pathogens .…”
mentioning
confidence: 99%
“…Previous reports have described biopsy findings of necrotic myocytes with minimal surrounding infiltration, acute lymphocytic infiltrate, 20 or mixed inflammatory infiltrate, often macrophage-predominant with some T cells. 21 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%